Persepsi Masyarakat Terhadap Kualitas Pelayanan Samsat Dumai - Hildawati Hildawati (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
One of the roles of government agencies is to carry out public services. This includes the Samsat Dumai which is responsible for providing services in the management of the issuance of driving letters such as STNK and TNKB. In its implementation, this service has received a lot of public response, especially the comfort of the service room and the attitude of the apparatus in the service process which is considered less responsive. For this reason, this study seeks to describe people's perceptions about: Performance Theory used is the opinion of Berry and Parasuraman in Mu'ah and Masram (2014: 24) service quality can be seen through five things including: 1) tangible 2) reliability, 3) power responsive, 4) certainty, and 5) empathy. Data collection techniques are observation, questionnaires and interviews. The sample used was 120 people with the incidental sampling technique. Data analysis using descriptive statistics. From the results of the study, it was obtained that the responses of respondents about the community's perception of the quality of service were good with a total score obtained of 10,565 which was in the score range 10,200 - 12,599. Or when viewed by the percentage, there are 40, 23% of respondents who stated that the quality of Samsat services was categorized as Good